다중지능에 의한 부모 - 교사의 유아 잠재능력 평가간의 인식비교 연구 - 김명희(Myoung Hee Kim); 신화식(Hwa Sik Shin) (Korean Journal of child studies, 2001)
This research analyzed differences between parents and teachers in assessment of young children's potential abilities based on multiple intelligences theory. Subjects were 10 boys and 10 girls, 4 and 5 years of age and their parents and teachers. Children's potential abilities were measured by the Korean Project Spectrum(KPS) and by the assessments of parents and teachers. Data were analyzed by SPSS. Statistical methods were Cronbach's ${α}$, t-test, and Pearson's and Spearman's correlations. Results revealed differences between the assessments of parents and of teachers. While teacher assessments were very similar to the results of the KPS on logical mathematical and linguistic intelligence, the results of parents' assessments were different from the results of the KPS on musical, interpersonal-intrapersonal, and naturalistic intelligence.